A New Purification Process of Solanesol Based on Chemically Modified Diatomite. Issue 1 (1st January 2022) - Liu, Jing; Han, Xiaobin; Peng, Yulong; Wang, Xiaoyan; Qiao, Runmeng; Liu, Jialei
Abstract: Diatomite is a kind of natural material with adsorption capacity and it's widely used in industry. The main purpose of this paper is to study the influence of hydrochloric acid concentration and modification time on the modification effect of diatomite. This article describes a modified method of diatomite, which can not only reduce the purification cost, but also improve the separation efficiency of solanesol. The results show that when the concentration of hydrochloric acid is 3mol/L and the treatment time is 50 minutes, the modification effect of diatomite is the best. The determination of the optimum technological conditions is conducive to the separation and purification of Solanesol by diatomite, and lays a foundation for the further development and utilization of diatomite.